Maps to the stars [videorecording (DVD)] - Cusack, John, 1966-; Moore, Julianne; Wasikowska, Mia, 1989-; Pattinson, Robert, 1986- ([Publisher not identified], 2015)
Meet the Weiss family, who are making their way in Hollywood rife with money, fame, envy, and relentless hauntings. Stafford Weiss is a famed TV self-help therapist with an A-list celebrity clientele. Meanwhile, Cristina Weiss has her work cut out managing the career of their disaffected child-star son, Benjie, a fresh graduate of rehab at age thirteen. Yet unbeknownst to them, another member of the Weiss family has arrived in town, mysteriously scarred and tormented, Agatha.